2006
DOI: 10.1007/bf02708419
|View full text |Cite
|
Sign up to set email alerts
|

On the conspecificity ofAnopheles fluviatilis species S withAnopheles minimus species C

Abstract: Anopheles fluviatilis and An. minimus complexes,each comprising of at least three sibling species, are closely related and important malaria vectors in Oriental Region. Recently An. fluviatilis species S, which is a highly efficient malaria vector in India, has been made conspecific with An. minimus species C (senior synonym) on the basis of homology in 335 base pair nucleotide sequence of D3 domain of 28S ribosomal DNA (rDNA). We examined the conspecificity of these two nominal species by obtaining and analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…minimus C based on appreciable differences in the sequences of the second internal transcribed spacer (ITS2) locus and D2-D3 domain of 28S rDNA. Singh et al (2006) also documented the presence of species C in central Myanmar. Harbach (2004) pointed out that little progress has been made in giving formal names to members of sibling species complexes in cases where the availability of junior synonyms of the nominotypical species must be considered.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…minimus C based on appreciable differences in the sequences of the second internal transcribed spacer (ITS2) locus and D2-D3 domain of 28S rDNA. Singh et al (2006) also documented the presence of species C in central Myanmar. Harbach (2004) pointed out that little progress has been made in giving formal names to members of sibling species complexes in cases where the availability of junior synonyms of the nominotypical species must be considered.…”
Section: Introductionmentioning
confidence: 91%
“…More recently, however, the occurrence of An. minimus C in India was refuted by Singh et al (2006) who showed that An. fluviatilis S is distinct from An.…”
Section: Introductionmentioning
confidence: 99%
“…paraliae from Thailand, based on ITS2 sequences, was in accordance with previous reports of different groups of Anopheles, e.g., the Anopheles gambiae complex (0.4-1.6%) (Paskewitz et al 1993), Anopheles dunhami and Anopheles nuneztovari (mean genetic distance = 0.025) (Ruiz et al 2010), Anopheles fluviatilis S and An. minimus C (pairwise distance = 0.036) (Singh et al 2006), Anopheles kunmingensis and Anopheles liangshanensis (pairwise distance = 0.0381) and An. pullus (= An.…”
Section: Discussionmentioning
confidence: 99%
“…minimus C based on comparison of the D3 domains of 28S (28S-D3) (Harbach 2004, Garros et al 2005, Chen et al 2006). However, Singh et al (2006) carried out molecular analysis on ITS2 and D2-D3 domains of 28S rDNA regions of An. fluviatilis S and An.…”
Section: Discussionmentioning
confidence: 99%
“…minimus species C (senior synonym) on the basis of homology in the 335 base pair nucleotide sequence of the D3 domain of the 28S gene [9,20]. However, this idea was refuted by Singh et al [21] who showed that An. fluviatilis S is distinct from An.…”
Section: Discussionmentioning
confidence: 99%